Incorporation of kiwifruit peel improved the property of carboxymethyl cellulose-gum Arabic active film and its effects on the quality of beef sausages - Evans Frimpong Boateng; Ziyi Yang; Jian Zhang; Lei Zhou; Lujuan Xing; Wangang Zhang (Food Production, Processing and Nutrition)
Abstract In the present study, different doses of lyophilized kiwifruit peel powder extract (KPE) were incorporated into carboxymethyl cellulose (CMC) and gum Arabic (GA) based polymer matrices to fabricate films CG-CT (control film), CG-KPE1 (1% KPE), CG-KPE2 (2% KPE), and CG-KPE3 (3% KPE) to investigate their effects on active packaging functionality and sliced-beef sausage quality. Consequently, CG-KPE films demonstrated a superior antimicrobial effect on Gram-positive (Staphylococcus aureus and Bacillus cereus) and Gram-negative (Escherichia coli) bacteria and antioxidant efficacy compared to CG-CT films. The scanning electronic microscopy (SEM) of CG-KPE films revealed an enhanced micrograph. Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) evidenced the intramolecular interaction between KPE and CG and the improved thermal stability of film matrix. Film X-ray diffraction (XRD) peaks revealed a good crystallinity. CG-KPE films exhibited better physical and mechanical properties, increased opacity, and better ultraviolet (UV) emission barrier due to KPE addition and pigmentation compared to CG-CT films. The quick biodegradability of CG-KPE film suggested potential for KPE as a biopolymer. Subsequently, sliced-beef sausages were packaged with CG-CT, CG-KPE1, CG-KPE2, and CG-KPE3 (respective to CT, TI, T2, and T3) and stored for 12 d (4 ± 1 °C). The product’s pH and moisture content were controlled due to KPE addition in CG-KPE films. The products revealed that during storage CG-KPE treatments had a positive impact on the textural property, the color stability, and the sensory quality compared to CG-CT treatments. CG-KPE treatments showed antimicrobial effectiveness and lesser TBARS values than CG-CT treatments during storage. Graphical Abstract